International clinician perspectives on pandemic-associated stress in supporting people with intellectual and developmental disabilities. Issue 3 (18th May 2022) - Howkins, Joshua; Hassiotis, Angela; Bradley, Elspeth; Levitas, Andrew; Sappok, Tanja; Sinai, Amanda; Thakur, Anupam; Shankar, Rohit
Abstract : Background: People living with intellectual and developmental disabilities (IDD) have suffered disproportionately in health outcomes and general well-being during the COVID-19 pandemic. There is emerging evidence of increased psychological distress. Increased strain has also fallen on clinicians managing the psychological needs of people with IDD, in the context of learning new technologies, staff shortages, reduced services and paused training opportunities. Aims: To examine clinicians' experiences of patient care, clinical management and the impact of care delivery. Method: A mixed fixed-response and free-text survey comprising 28 questions covering four areas (responder demographics, clinical practice, changes to local services and clinician experiences) was developed, using the STROBE guidance. It was disseminated through an exponential snowballing technique to clinicians in seven high-income countries. Quantitative data were analysed and presented with Microsoft Excel. Qualitative data were coded and thematically analysed, and presented with in-text quotations. Results: There were 139 respondents, mostly senior physicians (71%). Two-thirds reported over 10 years working in the field. Quantitative findings include increased clinician stress (77%), referrals (53%), patient distress presentations (>70%), patient isolation (73%) and carer burden (89%), and reduced patient participation in daily activities (86%). A third reported increased psychotropic prescribing. Qualitative analysis outlined changes to clinical practice, particularly the emergence and impact of telehealth. Conclusions: In the countries surveyed, the pandemic has not only had a significant impact on people with IDD, but also their carers and clinicians. A proactive, holistic international response is needed in preparedness for future public health emergencies.